The anti-religious policy of the soviet state in the context of the involvement of the peoples of the North Caucasus in the bolshevik modernization of the 1920s. - Natalia Kh. Dzagurova; Marina S. Gapeeva (Кавказология)
The article examines the methods and forms of the anti-religious policy of the Soviet state to involve the peoples of the North Caucasus in the Bolshevik modernization of the 1920s. The relevance of studying the history of the anti-religious policy of the state in order to avoid mistakes in a difficult period of transformation that is going through modern multinational and multi-confessional Russian society dictates the appeal. The purpose of the study is to examine the Soviet state policy in the fight against religion in the North Caucasus and analyze the methods and forms of anti–religious propaganda used. The research was based on material drawn from periodicals and archives of the North Caucasus. The complex of measures implemented by the state in the period under study to re-evaluate the old norms of existence and the formation of social ideas in the public consciousness based on the elimination of religious thinking is analyzed. The study reveals difficulties in implementing Bolshevik modernizations due to the population’s diverse national and religious backgrounds and the limited number of people engaged in social production. The key markers of anti-religious propaganda have been identified, the results of which led to the accelerated development of productive forces and the social sphere in the national regions of the North Caucasus according to Soviet ideology.